Non-destructive evaluation of reinforced concrete structures. Volume 2, - Maierhofer, Christiane; Reinhardt, Hans-Wolf; Dobmann, Gerd (Woodhead Publishing in materials., 2010)
"This book reviews the latest non-destructive testing techniques for reinforced concrete structures and how they are used. Part One discusses planning and implementing non-destructive testing of reinforced concrete structures with chapters on non-destructive testing methods for building diagnosis, development of automated NDE systems, structural health monitoring systems and data fusion. Part Two reviews individual non-destructive testing techniques. Part Three covers case studies including inspection of concrete retaining walls using ground penetrating radar, acoustic emission and impact echo techniques and using ground penetrating radar to assess an eight-span post-tensioned viaduct. This volume is a standard reference for civil and structural engineers as well as those concerned with making decisions regarding the safety of reinforced concrete structures."--Knovel.